Different expressions of the crustal structure across the Dongsha Rise along the northeastern margin of the South China Sea. (March 2019) - Gao, Jinwei; Peng, Xuechao; Wu, Shiguo; Lüdmann, Thomas; McIntosh, Kirk; Ma, Benjun; Xu, Ziying
Graphical abstract: Highlights: Different structures are detected from the shelf to lower slope/oceanic basin. Continental crust was confirmed below the lower slope in the eastern Dongsha Rise. Pure-shear deformation and lower crustal flow led to the wide continental margin. Abstract: This study presents two long-cable, deep-penetration, multi-channel seismic reflection images and associated gravity modeling to delineate structures and magmatic features that occur along the margins of the eastern and western Dongsha Rise in the northeast South China Sea (SCS). These data show approximately symmetrical sags imaged on the shelf, but the structures begin to vary in multiple ways along the eastern and western Dongsha Rise after crossing the continental shelf. At the slope break, an anticline with two thrust faults and a Mesozoic unconformity are imaged on the eastern Dongsha Rise, whereas negative flower structures are detected on the western Dongsha Rise. Most large-scale normal faults sole into a mid- or lower-crustal detachment below the lower slope on the eastern Dongsha Rise whereas some uplifts with small fault offsets were imaged at the lower slope and seaward-dipping tilted fault blocks were imaged between the lower slope and oceanic basin on the western Dongsha Rise. Magmatism, expressed by different types, such as intrusions, volcanoes and sills, was active since at least 5.5 Ma; and magmatic deposits appear to be well-developed on the eastern Dongsha Rise of the northeastern SCS margin. Gravity modeling showed that the crust below the lower slope/oceanic basin in the eastern Dongsha Rise is hyper-extended continental crust underplated by a high velocity layer with a maximum thickness of 9.4 km below the slope break, rather than thickened oceanic crust. The continent-ocean transition zone (COT) has a broader extent on the eastern Dongsha Rise compared to the western Dongsha Rise. Pure-shear deformation and lower crustal flow have led to the formation of the crustal structural contrasts and the wide northeastern continental margin of the SCS.